Sonographically Assisted Percutaneous Removal of Screws in Dynamization of the Interlocking Intramedullary Nail. (1st February 2013) - Wu, Po-Ting; Lin, Cheng-Li; Tai, Ta-Wei; Shao, Chung-Jung; Wu, Kuo-Chen; Chern, Tai-Chang; Jou, I-Ming
Abstract : Objectives: Dynamization is a method of removing the interlocking screw(s) farthest from the fracture site for improving healing in femoral and tibial fractures that show delayed healing after static interlocking nailing. We describe a simple sonographically assisted technique for percutaneous dynamization of deep‐seated impalpable screws. Methods: Between March 2001 and March 2005, 20 dynamization procedures were completed using the developed technique under the diagnosis of delayed healing or a nonunion at a mean of 4.8 months after index surgery. After adequately positioning the involved leg, the transducer was placed on the area of the inlet of the screw. Longitudinal and transverse sonographically scanned sections, used to show the head of the screw, were then marked on the skin where the two sections intersected. After this precise marking, a small incision on the mark allowed insertion of the screwdriver and easy percutaneous removal of the screw using only local anesthesia for pain control. Results: We removed 31 screws: 9 proximal femoral screws, 20 distal femoral screws, and 2 proximal tibial screws. The mean depth of the screws was 3.4 cm. The mean operation times were 1.6 minutes for the sonographic examination and 3.5 minutes for removal of one screw. No infections or morbidities were caused by the procedure. Conclusions: Sonography is an effective tool for localizing a locked screw and facilitates percutaneous removal of screws under only local anesthesia for dynamization. This method needs no special instruments and reduces the time needed for dissecting the tissue and locating the screw.